Screening and Isolation of a Novel Polyene-Producing Streptomyces Strain Inhibiting Phytopathogenic Fungi in the Soil Environment - Park, Heung-Soon; Nah, Hee-Ju; Kang, Seung-Hoon; Choi, Si-Sun; Kim, Eung-Soo (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial-based eco-friendly biological substances are needed to protect crops from phytopathogenic fungi and replace toxic chemical fungicides that cause serious environmental issues. This study screened for soil antifungal Streptomyces strains, which produce rich, diverse, and valuable bioactive metabolites in the soil environment. Bioassay-based antifungal screening of approximately 2,400 Streptomyces strains led to the isolation of 149 strains as tentative antifungal producers. One Streptomyces strain showing the most potent antifungal activities against Candida albicans and Fusarium oxysporum was identified as a putative anti-phytopathogenic soil isolate that is highly homologous to Streptomyces rubrisoli (named S. rubrisoli Inha 501). An in vitro antifungal assay, pot-test, and field-test against various phytopathogenic fungi confirmed that S. rubrisoli Inha 501 is a potential novel phytopathogenic fungicide producer to protect various crops in the soil environment. Whole-genome sequencing of S. rubrisoli Inha 501 and an anti-SMASH genome mining approach revealed an approximately 150-kb polyene biosynthetic gene cluster (BGC) in the chromosome. The target compound isolation and its BGC analysis confirmed that the target compound responsible for the anti-phytopathogenic activity was a giant linear polyene compound highly homologous to the previously reported neotrafibiricin A. These results suggest that a bioassay-based screening of a novel antifungal Streptomyces strain followed by its genome mining for target compound BGC characterization would be an efficient approach to isolating a novel candidate phytopathogenic fungicide that can protect crops in the soil environment.